Associations of luteal phase changes in vagally mediated heart rate variability with premenstrual emotional changes - Schmalenberger, Katja; Eisenlohr-Moul, Tory A.; Jarczok, Marc N.; Schneider, Ekaterina; Barone, Jordan C.; Thayer, Julian F.; Ditzen, Beate (BMC women's health, 2024)
A recent meta-analysis revealed that vagally mediated heart rate variability (vmHRV; a biomarker of emotion regulation capacity) significantly decreases in the luteal phase of the menstrual cycle. As two follow-up studies suggest, these vmHRV decreases are driven primarily by increased luteal progesterone (P4). However, analyses also revealed significant interindividual differences in vmHRV reactivity to the cycle, which is in line with longstanding evidence for interindividual differences in mood sensitivity to the cycle. The present study begins to investigate whether these interindividual differences in vmHRV cyclicity can explain who is at higher risk of showing premenstrual emotional changes. We expected a greater degree of midluteal vmHRV decrease to be predictive of a greater premenstrual increase in negative affect.
Gesehen am 07.07.2025